Inflammatory myofibroblastic lung tumor: its birth, its bleeding growth, its difficult diagnosis and its surgical end in a child. Issue 8 (6th June 2018) - Pecoraro, Luca; Clemente, Maria; Tadiotto, Elisa; Piacentini, Giorgio; Pietrobelli, Angelo; Degani, Daniela
Key Clinical Message: The diagnosis of inflammatory myofibroblastic tumor is based on radiology and histology. The treatment is surgical, and the prognosis is good. For this reason, although this lung disease is rare, when a child show up at hospital with an unknown hemoptysis, this medical condition should not be underestimated. Abstract : The diagnosis of inflammatory myofibroblastic tumor is based on radiology and histology. The treatment is surgical, and the prognosis is good. For this reason, although this lung disease is rare, when a child show up at hospital with an unknown hemoptysis, this medical condition should not be underestimated.